Molecular analysis of enhanced replication of UV-damaged simian virus 40 DNA in UV-treated mammalian cells. - Treger, J M (1988)
Irradiation of simian virus 40 (SV40)-infected cells with low fluences of UV light (20 to 60 J/m2, inducing one to three pyrimidine dimers per SV40 genome) causes a dramatic inhibition of viral DNA replication. However, treatment of cells with UV radiation (20 J/m2) before infection with SV40 virus enhances the replication of UV-damaged viral DNA. To investigate the mechanism of this enhancement of replication, we analyzed the kinetics of synthesis and interconversion of viral replicative intermediates synthesized after UV irradiation of SV40-infected cells that had been pretreated with UV radiation. This enhancement did not appear to be due to an expansion of the size of the pool of replicative intermediates after irradiation of pretreated infected cells; the kinetics of incorporation of labeled thymidine into replicative intermediates were very similar after irradiation of infected control and pretreated cells. The major products of replication of SV40 DNA after UV irradiation at the low UV fluences used here were form II molecules with single-stranded gaps (relaxed circular intermediates). There did not appear to be a change in the proportion of these molecules synthesized when cells were pretreated with UV radiation. Thus, it is unlikely that a substantial amount of DNA synthesis occurs past pyrimidine dimers without leaving gaps. This conclusion is supported by the observation that the proportion of newly synthesized SV40 form I molecules that contain pyrimidine dimers was not increased in pretreated cells. Pulse-chase experiments suggested that there is a more efficient conversion of replicative intermediates into form I molecules in pretreated cells. This could be due to more efficient gap filling in relaxed circular intermediate molecules or to the release of blocked replication forks. Alternatively, the enhanced replication observed here may be due to an increase in the excision repair capacity of the pretreated cells.